2022
DOI: 10.1016/j.jare.2021.03.009
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of hydroxyapatite nanorods on graphene oxide nanosheets and their reinforcement in biopolymer scaffold

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(58 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…It is well known that the interface characteristics between the reinforcement and matrix play a crucial role in composites, especially for mechanical performance [34] , [35] , [36] , [37] . Many researches have demonstrated that by in situ interface reaction, a strong interface bonding could form between the matrix and reinforcement, which can improve the mechanical performance [34] , [38] .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the interface characteristics between the reinforcement and matrix play a crucial role in composites, especially for mechanical performance [34] , [35] , [36] , [37] . Many researches have demonstrated that by in situ interface reaction, a strong interface bonding could form between the matrix and reinforcement, which can improve the mechanical performance [34] , [38] .…”
Section: Resultsmentioning
confidence: 99%
“…It could be believed that there was strong interfacial adhesion in PLLA/g-HAP specimens to promote the effective stress transfer from PLLA to g-HAP, and hence the PLLA/g-HAP specimens showed good mechanical properties. 43,44 In addition, the surface morphologies of PLLA/HAP, PLLA/g1-HAP, PLLA/g2-HAP and PLLA/g3-HAP specimens are presented in Fig. 7(e1–e4), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…And the AZ61‐ x MgF 2 alloys were prepared through layer‐by‐layer manufacturing. [ 52 ] During laser melting process, Ar gas was used to provide a protective atmosphere with pressure of about 1.5 MPa.…”
Section: Methodsmentioning
confidence: 99%